Impact of nonlinear lighting loads on the neutral conductor current of low voltage residential grids - Hernández, Jairo (2020)
In the last decade, mainly due to political incentives towards energy efficiency, the share of lamps with power electronic interfaces, like Compact Fluorescent Lamps (CFL) and Light Emitting Diode (LED) lamps, has significantly increased in the residential sector. Their massive use might have a substantial impact on harmonic currents and, consequently, on the current flowing in the neutral conductor. This paper analyzes the impact of modern energy-efficient lighting technologies on the neutral conductor current by using a synthetic Low Voltage residential grid. Different load scenarios reflecting the transition from incandescent lamps, via CFL, to LED lamps are compared concerning the neutral conductor current at different points in the network. The inherent randomness related to the use of lighting devices by each residential customer is considered employing a Monte Carlo simulation. Obtained results show that the use of CFL has a greater impact on the neutral conductor current of Low Voltage (LV) residential grids and that, with increasing use of LED lamps, a decreasing impact can be expected in the future.